2014
DOI: 10.1111/tan.12472
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐DQ2/DQ8 and HLA‐DQB1*02 homozygosity typing by real‐time polymerase chain reaction for the assessment of celiac disease genetic risk: evaluation of a Spanish celiac population

Abstract: Celiac disease (CD) is a complex autoimmune disorder caused by ingestion of gluten in genetically susceptible individuals. Different genetic risk factors have been identified, but virtually all patients are human leukocyte antigen (HLA)-DQ2 and/or HLA-DQ8 positive. We describe a new, fast, accurate and simple real-time polymerase chain reaction (PCR)-based assay for the genotyping and homozygosity analysis of the CD-related HLA alleles. The assay overcomes the major limitations of protocols currently in use, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Vice versa in HLA-DQ high risk, but mainly in intermediate HLA-DQ risk subjects, carriage of any TNFA haplotype different from group A increased the predicted probability of disease and this increase appeared to be progressively higher in groups from B to E. Therefore TNFA genetic testing might be suggested as being of some help in improving CD risk assessment and in further studying patients. Interestingly, while HLA-DQ was not significantly associated with the histopathological lesion severity, in agreement with Ruiz-Ortiz et al [ 43 ], TNFA haplotype A to E showed a negative trend of association with severity of lesions. In other words, the progressive increase in CD risk due to TNFA haplotypes is associated with a progressive less severe histopathology.…”
Section: Discussionsupporting
confidence: 89%
“…Vice versa in HLA-DQ high risk, but mainly in intermediate HLA-DQ risk subjects, carriage of any TNFA haplotype different from group A increased the predicted probability of disease and this increase appeared to be progressively higher in groups from B to E. Therefore TNFA genetic testing might be suggested as being of some help in improving CD risk assessment and in further studying patients. Interestingly, while HLA-DQ was not significantly associated with the histopathological lesion severity, in agreement with Ruiz-Ortiz et al [ 43 ], TNFA haplotype A to E showed a negative trend of association with severity of lesions. In other words, the progressive increase in CD risk due to TNFA haplotypes is associated with a progressive less severe histopathology.…”
Section: Discussionsupporting
confidence: 89%
“…The highest risk for CD, 1:14, was found in risk group 1 (two DQ2, DR3-DQ2 or DR3/DR7-DQ2, with homozygous β2). For HLA-DQ8, a different trend, as compared with Italian [ 9 ] and Spanish [ 14 ] populations, was evidenced: this is probably because of a different frequency of DQ8 found in Moroccan controls, as in some other populations: in both Moroccans and Libyans, DQ8 genotypes and haplotypes showed a high frequency in the controls, and consequently the CD risk was lower than in other populations for this genotype. This changes the risk for CD of patients with the DQ8 genotype, which seems higher in Italians and in other populations than in Moroccans.…”
Section: Resultsmentioning
confidence: 94%
“…It can develop at any age as a result of an inherited (polygenic) disposition and exposure to gluten. Research carried out during the last two decades has shown that a central role in the occurrence of the disease is played by MHC class II HLA antigens: HLA-DQ2 and HLA-DQ8[ 6 ]. The absence of HLA-DQ2 and HLA-DQ8 has a strong negative predictive value for CD[ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gliadin antibody test and IgG class anti-TG2 antibody does not have the same specificity and clinical relevance. Use of a gluten-free diet is an effective treatment for CD as it has been shown to decrease the severity of clinical symptoms and reduce the risk of complications[ 6 - 8 , 15 ].…”
Section: Introductionmentioning
confidence: 99%